Management Practices During Perinatal Respiratory Transition of Very Premature Infants - Hallman, Mikko; Ronkainen, Eveliina; Saarela, Timo V.; Marttila, Riitta H. (Frontiers in Pediatrics, 2022)
Present review considers some controversial management practices during extremely premature perinatal transition. We focus on perinatal prevention and treatment of respiratory distress syndrome (RDS) in immature infants. 1. New concerns regarding antenatal corticosteroid management have been raised. Many fetuses are only exposed to potential adverse effects of the drug. The formulation and the dosage may need to be modified. Another challenge is to increase the fraction of the high-risk fetuses that benefit from the drug and to minimize the harmful effects of the drug. 2. Boosting anti-inflammatory and anti-microbial properties of surfactant requires further attention. Techniques of prophylactic surfactant administration at birth to extremely immature infants may be further refined. 3. New findings suggest that prophylactic treatment of PDA of a high-risk population rather than selective later closure of patent ductus arteriosus (PDA) may be preferred. TREOCAPA trial aims to study, whether prophylactic paracetamol improves the cardiorespiratory outcome and associates with long term benefit. 4. Is inhaled nitric oxide (iNO) used in excess? According to current evidence iNO treatment of uncomplicated RDS is not indicated. Considerably less than 10% of all very premature infants are affected by early persistence of pulmonary hypertension (PPHN). According to observational studies, effective ventilation combined with early iNO treatment are effective in management of this previously fatal disease. PPHN is associated with prolonged rupture of fetal membranes and with birth asphyxia. The LPS-induced immunotolerance as well as hypoxia-reperfusion induced oxidant stress may inactivate NO-synthetases in pulmonary arterioles and terminal airways. Prospective trials on iNO in management of PPHN are indicated. Other pulmonary vasodilators may be considered as comparison drugs or adjunctive drugs. Multidisciplinary challenge is to understand the regulation of pregnancy duration, and the factors participating the onset of extremely premature preterm deliveries and respiratory adaptation. Basic research aims to identify deficiencies in maternal and fetal tissues that both predispose to very preterm births and deteriorate the respiratory adaptation of immature infants. Better understanding on causes and prevention of extremely preterm births would eventually provide effective antenatal and neonatal management practices required for the intact survival.